POSTOPERATIVE DELIRIUM AMONG ELDERY PATIENTS - Borges, Eva (2022)
Background: Postoperative Delirium (POD) is defined as the occurrence of delirium among patients undergoing surgery, being particularly common among the elderly. This study focused on the incidence of POD among elderly patients admitted to a General Surgery ward. Methods: This was a prospective study among elderly patients admitted to a General Surgery ward. Neurologic assessments were carried out among patients aged 65 years and above, with a minimum hospital stay of four days. Patients undergoing surgical procedures were included in the study group; patients treated medically formed the control group. We collected demographic and clinical data and a Mini-Mental State Examination (MMSE) and Confusion Assessment Method 3-Minute (3D-CAM) were performed. Results: The incidence of delirium among elderly patients was 10%, the incidence of POD in elderly patients undergoing surgery was 14.9% versus 4.7% in patients undergoing medical treatment. Older age, higher Charlson Comorbidity Index (CCI), and a lower MMSE were significant for the development of delirium. Surgery implied an odds ratio of 3,588 showing a trend towards a greater occurrence of delirium among elderly patients undergoing surgery. Conclusions: POD’s is an important and common complication whose etiology is multifactorial. This study seems to be in accordance with the literature regarding the impact of aging, cognitive basal state, and comorbidity burden on the vulnerability that renders patients prone to the development of an acute confusional state.